Refocusing on the Success Enabling Factors in Mergers and Acquisitions - Anthony Okafor (European Scientific Journal, ESJ, 2019)
Mergers and acquisitions have continued to serve as a primary financing tool undertaken by organizations to achieve corporate objectives. Despite the increased popularity of the mergers and acquisitions phenomenon, determining acceptable metrics for identifying successful mergers and acquisitions continue to pose challenges to investors, financial analysts and other stakeholders involved with mergers and acquisitions. Mergers and acquisitions activities have presented mixed outcomes to different organizations with high failure rates recorded in some and less-significant successes reported in others. Consequently, understanding acceptable metrics for determining a successful merger or acquisition becomes paramount given the challenges experienced by players in that industry. Therefore, a thorough review of the literature is made in this study to identify factors that improve the chances of mergers and acquisitions success. The unique features of successful and unsuccessful mergers and acquisitions are itemized to provide a premise for assessing and evaluating the essential characteristics that make mergers and acquisitions successful. The importance of due diligence, low acquisition purchase premiums, and related business acquisitions in the mergers and acquisitions process were fully explicated. Low acquisition purchase premiums, timing of mergers and acquisitions and related business acquisitions were found to tremendously enhance the success of mergers and acquisitions.